2003
DOI: 10.1104/pp.103.025981
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mannuronan C-5-Epimerase Genes from the Brown Alga Laminaria digitata  

Abstract: Alginate is an industrially important polysaccharide obtained commercially by harvesting brown algae. The final step in alginate biosynthesis, the epimerization of ␤-1,4-d-mannuronic acid to ␣-1,4-l-guluronic acid, a structural change that controls the physicochemical properties of the alginate, is catalyzed by the enzyme mannuronan C-5-epimerase. Six different cDNAs with homology to bacterial mannuronan C-5-epimerases were isolated from the brown alga Laminaria digitata (Phaeophyceae). Hydrophobic cluster ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 50 publications
5
121
1
Order By: Relevance
“…These evolutionary constraints likely explain the loss of acetyl groups in algal alginates together with the increased importance of the G units and of their interactions with calcium ions to control gel properties. This hypothesis is consistent with the expansion of the mannuronan C5-epimerase gene families observed in the brown algae Laminaria digitata (17)(18)(19) and E. siliculosus (13).…”
supporting
confidence: 88%
“…These evolutionary constraints likely explain the loss of acetyl groups in algal alginates together with the increased importance of the G units and of their interactions with calcium ions to control gel properties. This hypothesis is consistent with the expansion of the mannuronan C5-epimerase gene families observed in the brown algae Laminaria digitata (17)(18)(19) and E. siliculosus (13).…”
supporting
confidence: 88%
“…Finally, model evaluation confirmed that AlgG is likely to have the RH␤H fold. A recent study using hydrophobic cluster analysis showed that an epimerase from the marine brown alga Laminaria digitata has a secondary structure similar to that of P. aeruginosa AlgG (46). Our modeling studies also show a similar fold for the A-module of the extracellular alginate epimerases from A. vinelandii (data not shown).…”
Section: Discussionsupporting
confidence: 61%
“…Even in samples with the highest conversion, the longest homopolymeric G-blocks are still much shorter than what we find in alginate from algae. We have shown earlier 18 of genes coding for epimerases 31 , but no single enzyme has yet been expressed and characterized. It is however established that the G-content increase associated with the age of algal tissue, suggests that long G-blocks are synthesized over an extended period of time.…”
Section: Discussionmentioning
confidence: 99%